2016
DOI: 10.1002/ange.201510879
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic Transformations from Norrole to Isonorrole and an N‐Confused Corrole with a Fused Hexacyclic Ring System Triggered by a Pyrrole Substituent

Abstract: Three kinds of fused porphyrinoids, L2-L4,p ossessing different types of corrole-based frameworks were synthesized from apyrrole-substituted corrole isomer (norrole L1). Oxidation of L1 afforded aunique N-C meso -fused pyrrolyl isonorrole L2,involving the fusion of an auxiliary pyrrolic NH moiety with ameso-sp 3 -hybridized carbon atom. Subsequently, L2 underwent macrocycle transformations to give singly and doubly N-C Ar -fused N-confused corroles, L3 and L4,r espectively. L3 and L4 contain fused [5.7.6.5]-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…24,25 Because the regioselectivity of the oxidative coupling reactions strongly depends on the distinct electronic structure (i.e., electron density) and steric factors, the elaborately designed porphyrin analogs with mislinked pyrrole units (e.g., α-β, α-β′, or N-β modes) in the corresponding scaffolds show selective reactivity. [26][27][28][29][30][31][32] Thus, chemical oxidation of N-confused porphyrin, 33,34 N-fused porphyrin, [35][36][37][38] neo-confused corrole (norrole), [39][40][41][42] and neo-confused hexaphyrin, 43,44 afforded the three-dimensional dimeric structures [45][46][47][48][49][50] with high regioselectivity via dehydrogenative C-C bond formation (Figure 1b). In this regard, we have previously demonstrated that the cyclization of a pentapyrrane with two terminal β-pyrrolyl units (P 5 ) afforded a highly twisted dihydrosapphyrin possessing a meso-sp 3 -carbon atom, which exhibited an unusual skeletal transformation reaction (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Because the regioselectivity of the oxidative coupling reactions strongly depends on the distinct electronic structure (i.e., electron density) and steric factors, the elaborately designed porphyrin analogs with mislinked pyrrole units (e.g., α-β, α-β′, or N-β modes) in the corresponding scaffolds show selective reactivity. [26][27][28][29][30][31][32] Thus, chemical oxidation of N-confused porphyrin, 33,34 N-fused porphyrin, [35][36][37][38] neo-confused corrole (norrole), [39][40][41][42] and neo-confused hexaphyrin, 43,44 afforded the three-dimensional dimeric structures [45][46][47][48][49][50] with high regioselectivity via dehydrogenative C-C bond formation (Figure 1b). In this regard, we have previously demonstrated that the cyclization of a pentapyrrane with two terminal β-pyrrolyl units (P 5 ) afforded a highly twisted dihydrosapphyrin possessing a meso-sp 3 -carbon atom, which exhibited an unusual skeletal transformation reaction (Figure 1c).…”
Section: Introductionmentioning
confidence: 99%
“…These originalm acrocycles belong to the innumerous class of contracted carbaporphyrinoids. [27][28][29] Thus the introduction of N-fused p-phenylene into am acrocyclic core, presumably by applying transition-metal cationsa s templating motif, can be treated asa no riginalw ay to generate au nique class of compounds with differento pticalr esponses,b ut more importantly with modified magnetic properties to play eventually arole in molecular devices. [30]…”
mentioning
confidence: 99%